(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
Th is paper analyses the concept of the culture of security and defence from the perspective of political science, studying the important implications and consequences of its defi nition based on the idea of political culture. on the other hand, also from this disciplinary viewpoint, it discusses the meanings of the terms culture of defence, culture of security and defence, and culture of security. in conclusion, it suggests a series of theoretical and conceptual proposals in order to achieve a better and more eff ective development of this public policy.